STRATEGI KOMUNIKASI BADAN PUSAT STATISTIK (BPS) KOTA PADANG DALAM MENSOSIALISASIKAN KEBIJAKAN SENSUS PENDUDUK KEPADA MASYARAKAT - Mila, Mila; Kohar, Wakidul; Indraddin, Indraddin (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted to find out the communication strategy carried out by the Padang City BPS in communicating the population census policy to the community. This research was based on the implementation of the 2010 population census policy which was a major event held simultaneously in all regions of Indonesia including the City of Padang. To achieve effective communication where all the people of Padang City are willing to participate in the success of the 2010 population census policy without being missed or not recorded, a carefully planned communication strategy is needed. The communication strategy that has been implemented by Padang City BPS managerially has gone through the stages of communication strategies starting from the planning stage to the evaluation. The form of communication conducted by BPS in Padang City in communicating census policies to the public is media communication, namely by socializing the population census policy through existing communication media. While the form of communication in communicating the population census policy to the community is face-to-face communication with the people of Padang City through structured interviews using questionnaire instruments.